Secondary level organisations and the democratisation of forest governance: Case studies from Nepal and Guatemala - Naya Sharma Paudel; Iliana Monterroso; Peter Cronkleton (Conservation & Society, 2012)
This paper examines the emerging role of secondary level organisations in the democratisation of forest governance by analysing two cases of forest-based collective action in Nepal and Guatemala. It explores the conditions surrounding the emergence and growth of these secondary level organisations, and examines the nature of their organisational approaches, strategic actions, and the resulting outcomes in terms of democratising forest governance. The organisations discussed in this paper are products of broader decentralisation processes and represent organised and empowered forest people. They are capable of shifting the balance of power in favour of community level institutions, and can compel state agencies to become more accountable to the needs of forest-dependent citizens. As a result, by leading collective action beyond the community to a secondary level, these organisations have influenced forest governance by making it more democratic, equitable and productive.